2013
DOI: 10.1097/nmd.0b013e3182848d04
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Alzheimer’s Disease Are Associated With Neuropsychiatric Symptoms and Antidementia Treatment

Abstract: Sleep disturbances (SDs) in Alzheimer's disease (AD) may significantly affect the behavioral, functional, and cognitive capacities of patients to the point of becoming a major determinant of caregiver burden. We conducted a cross-sectional study in 125 patients with probable AD to assess the association of SDs with neuropsychiatric symptoms, cognitive and functional status of patients, and severity and duration of dementia and to ascertain the role of antidementia drugs in the treatment of SD. SDs were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
1
28
0
4
Order By: Relevance
“…Our results are consistent with previous studies that found correlations between apathy and functional status [9, 1113] and between sleep and functional capacity [16, 17]. Apathy is commonly rated as a severe and frequent behavior on the NPI for individuals with AD [31] and strongly correlated to cognitive ability [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with previous studies that found correlations between apathy and functional status [9, 1113] and between sleep and functional capacity [16, 17]. Apathy is commonly rated as a severe and frequent behavior on the NPI for individuals with AD [31] and strongly correlated to cognitive ability [32].…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies have also associated higher frequency and severity of sleep disturbances with depression, disinhibition, or aberrant motor behavior [16]. In a previous study of AD patients with reported sleep disturbance on the NPI, better objective sleep was shown to be associated with better cognitive performance and functional status [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also had slightly lower MMSE scores than the AD group, but the clinical importance of the difference could be dubious (mean 23.8 vs. 23.0), especially since the groups had equal CDR scores. A higher total NPI score in DLB patients could also influence the severity of SD, although sleep pathology itself is an independent risk factor for the presence and severity of neuropsychiatric symptoms [24]. However, the most probable explanation is differences between DLB and AD at the neuropathophysiological level.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous results, García‐Alberca et al . demonstrated that sleep disturbances are also significantly associated with daytime behavioural disturbances, namely aberrant motor behaviour and disinhibition . Findings suggest that night‐time sleep is important for cognitive function and for behavioural and psychological symptoms of dementia in AD, and that sleep problems should be considered when treating AD patients because their treatment might improve cognitive function as well as behavioural and psychological symptoms of dementia …”
Section: Psychopathology and Sleep Disorders In Dementiamentioning
confidence: 98%